Design of Microstrip Patch Antenna for 5G - Sivabalan A, Pavithra S, Selvarani R, Vinitha K.M (International Journal of Control and Automation, 2020)
As the Telecommunication Systems are being updated, we design numerous antennas with various specifications. The millimetre wave band of 5G technology is exclusively used for high speed data transfer whose wavelength is in 1mm to 10mm range. Here we design and simulate a Microstrip Rectangular Patch Antenna (MPA) at 28 GHz frequency. The antenna design consists of a patch with 3.4 × 4.1 mm. In order to match the radiating patch and 50Ω feedline, an inset feed technique is used. In this design we have used Roger RT Duroid 5880 as a substrate material of relative permittivity 2.2 and height 0.5mm. As a result, we have obtained increased gain, return loss and VSWR. This proposed model is devised and analyzed using High Frequency Structure Simulator (HFSS) software.